The Role of Female Leadership in Enhancing School Performance (Case Study of SMK dr. Soebandi Jember) - Taufan Dwi Susilo; Moch Anas Kurniawan; Fitri Ayu Suryani (Medikun Publisher, 2024)
This study examines the role of female leadership in improving school performance at SMK dr. Soebandi Jember. The results indicate that the female principal at this school has a significantly positive impact on school performance through her unique and effective leadership style. The principal has a strong background in managing hospitals, pharmacies, and as a lecturer, which allows her to implement high standards in school management. In terms of human resource management, the principal categorizes teachers into two statuses: permanent teachers with additional structural duties and non-permanent teachers who only teach. This division facilitates control and monitoring of teacher performance through monthly reports that include lesson plans (RPP), teaching journals, attendance, and evaluations. In the aspect of learning, SMK dr. Soebandi Jember offers health-related study programs with strict student selection, including written tests and color blindness tests. The education is more focused on practical skills, supported by internship programs in collaboration with pharmacies, hospitals, and laboratories.Additionally, the principal fosters strong relationships with the healthcare and medical industries for student internship programs, enhancing student competencies in their respective fields. Collaborations have been established with various health and medical companies, including internship opportunities abroad, such as in Japan. Overall, female leadership at SMK dr. Soebandi Jember has successfully improved school performance through structured and innovative approaches in managing human resources, learning processes, and industry relations. This study demonstrates that female leadership has significant potential to bring about positive change and advancement in educational settings.